Comparative Evaluation of Independent Private Values Distributions on Internet Auction Performance - Leung,TLY; Knottenbelt,WJ (International Journal of E-Entrepreneurship and Innovation, 2012)
The Independent Private Values (IPV) model is foundational for the analysis of Internet auction performance and is widely used in the study of auction behaviour. The characteristics of this model include the assumptions of privacy and independence where the value of the commodity in question is private to the individual buyers, and that different buyers do not know the values other buyers attached to the commodity. In addition, these values are drawn from a common distribution which is known to the buyers. In probabilistic terms, this essentially amounts to a series of values which are independent and identically distributed. The features and characteristics of the IPV distribution will have a significant impact on auction behaviour, and since a general stochastic analysis of their impact is analytically intractable, here auction performance is studied using an auction process simulator. Both hard close and soft close Internet auctions are studied. In addition, Vickrey auctions and auction mechanisms with multiple bid acceptance are compared and evaluated. From experimental findings, the paper establishes quantitative relationships between the different auction process parameters, deploy suitable IPV distributions to model the characteristics of different communities of bidders, provide suggestions for optimising auction performance, and recommend strategies for efficient auction design.